Die Operisti als kulturelles Netzwerk: Der Briefwechsel von Franz und Marianne Pirker - Brandenburg, Daniel (Verlag der Österreichischen Akademie der Wissenschaften, 2021)
A critically annotated edition of the mid-18th century correspondence between the operisti and partners in marriage, Franz and Marianne Pirker.